Etiology of the membrane potential of rat white fat adipocytes - Bentley, Donna C.; Pulbutr, Pawitra; Chan, Sue; Smith, Paul A. (American Physiological Society, 2014)
The plasma membrane potential (Vm) is key to many physiological processes, however its ionic aetiology in white fat adipocytes is poorly characterised. To address this question, we have employed the perforated patch current-clamp and cell-attached patch-clamp methods in isolated primary white fat adipocytes and their cellular model: 3T3-L1. The resting Vm of primary and 3T3-L1 adipocytes were -32.1±1.2mV (n=95) and -28.8±1.2mV (n=87), respectively. Vm was independent of cell size and fat content. Elevation of extracellular [K+] to 50mM by equimolar substitution of bath Na+ did not affect Vm, whereas substitution of bath Na+ with the membrane impermeant cation N-methyl-D-glucamine+ hyperpolarized Vm by 16mV, data indicative of a non-selective cation permeability. Substitution of 133mM extracellular Cl- with gluconate, depolarised Vm to +5.5, whereas Cl- substitution with I- caused a -9mV hyperpolarization. Isoprenaline (10µM) but not insulin (100nM) significantly depolarized Vm. Single-channel ion activity was voltage independent; currents were indicative for Cl- with an inward slope conductance of 16±1.3pS (n=11) and a reversal potential close to the Cl- equilibrium potential: -29±1.6mV. Reduction of extracellular Cl- elevated the intracellular Ca2+ of adipocytes. In conclusion, the Vm of white fat adipocyte is well described by the Goldman-Hodgkin-Katz equation with a predominant permeability to Cl-. Consequently, changes in serum Cl- homeostasis or the adipocyte’s permeability to this anion via drugs will affect its Vm, intracellular Ca2+ and ultimately its function and its role in metabolic control.